Nuno Álvares Pereira, senhor de Almada - José Augusto C. F. Oliveira (Medievalista)
From Nuno Álvares Pereira's life path, were always highlighted his warlike actions and his religious virtues, although his performance as holder of jurisdictional powers over vast domains still remains unclear. When peace negotiations with Castile were definitively in line and his military services were no longer indispensable to the political declaration of D. João I and the defense of the kingdom, Nuno Álvares Pereira, who, as is known, never took root in any place, seems to focus its attention on Almada. He promoted a palace in the castle grounds, where he effectively resided, albeit for a short period, and made investments, which led to the disagreement of D. João I, and interfered in the council's life in various aspects, under the protection of his manorial powers. It was also in Almada that he tried to ensure the viability of the Carmo convent, where he would retire in 1423, the year following the donation of the town and term to his granddaughter Isabel.